HEAT TREATMENT TEMPERATURE INFLUENCE ON THE STRUCTURAL AND OPTICAL PROPERTIES OF BROOKITE TIO2 THIN FILM SYNTHESIZED USING GREEN SOL-GEL ROUTE - Johari, N.D.; Rosli, Z.M.; Juoi, J.M.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
Alcoholic solvents have disadvantages for the environment and the human body. Brookite film was deposited via green sol-gel route (without the use of any alcoholic solvent), in combination with different heat treatment temperatures, in order to study the effect of heat treatment temperature on structural and optical properties. Different heat treatment was studied at 200°C and 300°C. Brookite film formation was evaluated with X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), UV-Vis spectrometer and water contact angle measurement. X-ray diffraction (XRD) analysis revealed the formation of brookite (111) and (023) at 200°C and 300°C with a crystallite size of 47 nm and 58 nm, respectively. FTIR analysis also revealed Ti-O-Ti bonding at 400–800 cm-1. The band gap energy was 3.40 eV (200°C) and 3.37 eV (300°C). The water contact angle was 19.64° at 200 °C and 13.50° at 300°C, respectively. Therefore, via this green sol–gel route, a lower heat treatment temperature of 200°C was more preferable for the formation of single brookite compared to the common TiO2 sol formulation (with solvent) that required a high heat treatment temperature. Brookite was produced with a lower band gap and contact angle that contributed to better photocatalytic activity.